Clinical and Advocacy Implications of the Dobbs vs. Jackson Women's Health Organization Ruling on Trafficked Persons - Gautham, Ila (Violence against women, 2025)
The United States Supreme Court decision on the case of Dobbs vs. Jackson Women's Health Organization abolished federal protections of abortion, leaving abortion legislation at the discretion of individual states. Trafficked persons are a population especially vulnerable to the impacts of this ruling. Because there is no existing literature describing the effects of restrictive abortion legislation on this group, we described some of the potential consequences of restrictive abortion laws for sex and labor trafficked persons, based on real case examples. We describe steps that should be taken to sufficiently protect and support pregnant trafficked women in relation to the Dobbs law.